Distributive Justice and Richard Susskind’s Online Courts in the Brazilian Judicial System: an analysis of the Justice 4.0 Program - Santos Divino, Sthéfano Bruno (2024)
Richard Susskind’s Online Court is no longer just an ideal, but a policy for implementing and developing the judiciary alongside technology. Its application in the Brazilian legal system has been proposed, applied, improved, and constantly refined by the National Council of Justice. The aim is to understand the structuring legal concept of the Virtual Court, created by Richard Susskind, to identify its premises, foundations, and pretensions. It then shows how Susskind’s Virtual Court has been applied in the Brazilian legal system through the Justice 4.0 program. Finally, the current policies are briefly analyzed to verify their compatibility with due process of law. Thus, the research problem that guides this article and the proposed objectives can be expressed by the following question: has the Justice 4.0 Program complied with the foundations and fundamental precepts of Richard Susskind’s Virtual Courts, as well the Distributive Justice? The conclusion is that despite technological and legal advances, the Justice 4.0 Program is still precarious in terms of accessibility, transparency, and proportionality of justice. The method used is integrated research combined with bibliographical research.